Exploring the role of peroxisomes in Helicobacter pylori infection - Alves, Sandra Manuela Carvalho (2018)
The Helicobacter pylori is a gram-negative microaerophilic bacterium. Humans are the principal reservoir and it has been estimated that about 50% of the world population is infected by this bacterium, even though only about 20% of the patients present symptoms. The H. pylori colonizes the human gastric mucosa and is associated to several gastrointestinal diseases, such chronic gastritis, peptic ulceration and gastric cancer. Peroxisomes are membrane-enclosed subcellular organelles, which can be virtually found in all eukaryotic cells. They are involved in several metabolic reactions, with emphasis for the fatty acid oxidation, lipid biosynthesis and hydrogen peroxide detoxification. It is increasingly accepted that peroxisomes are more than simple metabolic organelles within cells. Previous studies of viral infections have demonstrated that peroxisomes are involved in the cellular innate immune response. It has also been suggested that all bacterial and viral pathogens may be exposed to peroxisomal recognition. Thus, it becomes important to better study the role of the peroxisomes in response to infections. In the present work we have analysed the possible peroxisomal alterations in morphology, number and enzymatic function in infected cells with the main aim of exploring a possible role for peroxisomes in H. pylori infection. The obtained results suggest that H. pylori infection does not affect significantly the peroxisomal morphology, number or localization. However, the results obtained suggested that H. pylori infection affects the amount of peroxisomal catalase, probably due to an increase of ROS in the cellular environment, as a consequence of the bacterial infection.